Menggali Kearifan Lokal: Hakikat Manusia menurut Pandangan Islam dalam Menjaga Alam dan Lingkungan - Fahrianto, M. Said; Sarjan, Muhammad (Lembaga Bale Literasi, 2025)
Ecology is a reciprocal relationship between organisms and their environment. This includes humans who were created by Allah, and entrusted with great responsibility as caliphs to prosper all life on earth. However, in reality, most humans do not realize that the relationship between humans and the environment is a relationship that has been determined and regulated by God. So in this study, the focus of the researcher's discussion is on how the nature of Islam views an ecological system. To facilitate this research, the researcher formulated the main problem, namely, how is the correlation between human life and the environment? And what is the nature of humans and the environment in the perspective of Islamic ecology.